THE IMPACT OF TECHNOLOGICAL ADVANCES ON THE DEVELOPMENT OF DIGITAL MARKETING ON TIKTOK: Received: 5th August 2024 Revised: 22nd August 2024, 3rd September 2024 Accepted: 10th August 2024 - Largo, Ghazy Rayhan (PEOPLE: International Journal of Social Sciences, 2024)
Technological advancements have revolutionized the marketing strategies employed by companies, particularly in the realm of digital marketing. Digital marketing utilizes digital technologies and online platforms to achieve more effective and efficient customer outreach on a global scale. This study aims to investigate the impact of technological progress on the evolution of digital marketing. Employing case studies from previous research, this study leverages the AIDA (Attention, Interest, Desire, and Action) framework to examine this relationship. The findings indicate a significant correlation between technological advancements and the growth of digital marketing, influenced by various factors. Furthermore, the rise of social media platforms, such as TikTok, has notably reshaped the digital marketing landscape. TikTok's unique structure and vast user base offer companies new opportunities to engage with their audience, create viral content, and boost brand awareness. The study highlights the importance of TikTok's algorithm, user engagement, and creative elements in enhancing digital marketing effectiveness, establishing it as a crucial tool for modern marketers.